Digital Public Relations Transformation, Brand Awareness, and Stakeholder Engagement in an Islamic Educational Institution: A Sequential Explanatory Mixed Methods Study - Rachman, Poppy; Aziz, Abd; Wisudaningsih, Endah Tri (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2026)
Purpose – This study examines associations among Digital Public Relations Transformation, Digital PR Maturity, Brand Awareness, and Stakeholder Engagement in one Islamic educational institution and develops a context-specific conceptual blueprint for digital PR management. Design/methods/approach – A sequential explanatory mixed-methods design combined a survey of 102 stakeholders analyzed using PLS-SEM with interviews and focus group discussions involving 12 participants. Religious Content was examined qualitatively as contextual evidence rather than as a statistical moderator. Findings – Digital PR Transformation was positively associated with Digital PR Maturity (β = .417, p < .001, R² = .174) and Brand Awareness (β = .268, p < .001). Digital PR Maturity was positively associated with Brand Awareness (β = .208, p < .001, R² = .162), while Brand Awareness was associated with Engagement (β = .468, p < .001, R² = .219). Qualitative accounts emphasized consistent academic-religious messaging, clear workflows, and interaction prompts. Because bootstrapped indirect-effect intervals are not reported, the results do not establish mediation. Research implication – The study offers a process-oriented, institution-specific blueprint for governance, content coordination, and analytics. The findings are associative and require replication, complete measurement-model reporting, and pilot implementation before broader generalization.